Role of information communication technology for evidence based medicine among physicians - Anwar, F. (Institute of Electrical and Electronics Engineers Inc., 2014)
In the current globalization age, Information communication technology (ICT) is diffusing its applications and services to every domain. The role of ICT in health care sector cannot be ignored as healthcare is directly associated with human lives. ICT empowers healthcare personnel in achieving high productivity and better accuracy in the clinical tasks by practicing evidence based medicine (EBM). This is a cross sectional quantitative study exploring the role of ICT and information systems for EBM. It is identified that clinical care personnel recognize the benefits to adopt ICT in the clinical educational workplaces for EBM. However they feel frustrated by workload preventing access to information technology, limitations of technology access and lack of opportunities for training in ICT. It is evident from this research that familiarity, use and self-confidence in the use of ICT is somewhat greater in personnel who have a recent tertiary education. Â© 2014 IEEE.